Tauhid as an Epistemology of Transformation: Reconstruction of Integrative-Holistic Counseling Based on Transcendental Values - Nadhiratul Ula; Naila Rofiqotul Afiyah; Muhammad Saiful Rijal; Ali Hasan Siswanto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Spiritual crises, moral disorientation, and the increasing prevalence of mental health problems in modern society indicate the limitations of conventional counseling paradigms, which tend to be positivistic and fragmented. Modern psychological approaches generally separate spiritual, psychological, and social dimensions, thereby failing to understand human beings holistically. On the other hand, the study of transcendental values in Islamic Studies, Theology, and Sufism remains largely normative and has not yet been constructed as an applicable paradigm for social transformation and contemporary counseling practice. This study aims to reconstruct tawhid as an epistemology of transformation through the model of Integrative-Holistic Tawhid Counseling based on transcendental values. The research employs a qualitative approach based on library research with philosophical, theological, and interdisciplinary analysis of literature in Islamic Studies, Islamic psychology, and contemporary Sufism. This article argues that tawhid is not merely a theological doctrine but an epistemological paradigm capable of integrating spiritual, psychological, and social dimensions simultaneously. Transcendental values are positioned as both a therapeutic foundation and a spirit of social transformation that shapes self-awareness, mental health, and human ethics. The scholarly contribution of this study lies in the development of a new paradigm, “Integrative-Holistic Tawhid Counseling,” which bridges the dichotomy between religion and modern psychology and presents a transformative counseling model based on Islamic spirituality in addressing the crises of modern humanity.